Burn injury as a result of interpersonal violence in the Northern Territory Top End. Issue 5 (August 2019) - Murphy, Lisa; Read, David; Brennan, Margaret; Ward, Linda; McDermott, Kathleen
Highlights: IPV burns comprise 7.4% of admissions to the Royal Darwin Hospital Burn Service. IPV burn victims are 2.3 times more likely to be female than non-IPV burn victims. IPV burn victims are 17 times more likely to be Indigenous than non-IPV burn victims. Victim alcohol or drug use is present in almost 60% of IPV cases. Approximately half of IPV burns are the result of family or domestic violence. Abstract: Aim: To describe the demographics, circumstances, burn wound characteristics and current tertiary centre management of interpersonal violence (IPV) burn victims in the Northern Territory Top End. It is anticipated that such knowledge gained will be of benefit to key stakeholders across the spectrum of injury prevention and management in this region. Methods: All adult admissions to the Royal Darwin Hospital (RDH) during 2010–2015 were identified through the Burns Registry of Australia and New Zealand. Demographic and burn characteristics were compared between those classified as IPV and non-IPV. Case note review provided supplementary data for the IPV subset. Results: Fifty-three patients met IPV criteria, comprising 7.4% of admissions to the RDH Burn Service. IPV burn victims were 2.3 times more likely to be female than those with non-IPV burn (95% CI: 1.2–4.3), and 17 times more likely to be Indigenous (95% CI: 7.9–35). Approximately half (53%) of IPV burns were classified as family or domestic violence; scalding was the most common mechanism in this group. Ten patients (19%) had incomplete burn care through self-discharge, all identified as Indigenous. Twenty percent of patients had no documented inpatient psychosocial support. Conclusions: Female and Indigenous persons are at increased risk of IPV burn. The challenges of providing care to the IPV burn population extend beyond burn wound closure.